2006
DOI: 10.1007/s00403-006-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of human tenascin-X domains with dermal extracellular matrix molecules

Abstract: Tenascin-X (TNX) is a large 450 kDa extracellular matrix protein expressed in a variety of tissues including skin, joints and blood vessels. DeWciency of TNX causes a recessive form of Ehlers-Danlos syndrome characterized by joint hypermobility, skin fragility and hyperextensible skin. Skin of TNX deWcient patients shows abnormal elastic Wbers and reduced collagen deposition. The mechanism by which TNX deWciency leads to connective tissue alterations is unknown. Here we report that C-terminal domains of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 27 publications
1
51
0
2
Order By: Relevance
“…12) TNX haploinsufficiency is associated with joint hypermobility type of EDS. 14) Previous studies have indicated several functional properties of TNX, including collagen fibrillogenesis, 15,16) collagen deposition, 17) and development and maintenance of elastic fibers. 18) As for the adhesive properties of bovine TNX in which the 10th FNIII repeat possesses an Arg-Gly-Asp (RGD) putative cell attachment sequence, Elefteriou et al 9,19) demonstrated that osteosarcoma (MG63) and bladder carcinoma (ECV304) cells adhere to bovine TNX weakly and that do not spread and do not assemble actin stress fibers.…”
mentioning
confidence: 99%
“…12) TNX haploinsufficiency is associated with joint hypermobility type of EDS. 14) Previous studies have indicated several functional properties of TNX, including collagen fibrillogenesis, 15,16) collagen deposition, 17) and development and maintenance of elastic fibers. 18) As for the adhesive properties of bovine TNX in which the 10th FNIII repeat possesses an Arg-Gly-Asp (RGD) putative cell attachment sequence, Elefteriou et al 9,19) demonstrated that osteosarcoma (MG63) and bladder carcinoma (ECV304) cells adhere to bovine TNX weakly and that do not spread and do not assemble actin stress fibers.…”
mentioning
confidence: 99%
“…Moreover, these authors used a small isoform lacking the central FNIII modules, whereas we produced the full-length protein comprising 30 FNIII domains. Interestingly, another group has shown that the 29 th FNIII module of TNX accelerates collagen fibrillogenesis [8], but this modulatory effect seems to be masked in…”
Section: Influence Of Tnx On Collagen Fibrillogenesismentioning
confidence: 99%
“…Considering the interaction of TNX with fibrillar collagens [7,8] and the elastic properties of TNX [9], we decided to examine the physical behaviour of the collagen gels formed in the presence of TNX by rheometry, and to compare them to control gels consisting of collagen alone, or collagen and BSA.…”
Section: Effect Of Tnx On the Mechanical Properties Of Collagen Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNX-deficient mice partly mimic this phenotype. 3) Several observations suggest that TNX is involved in collagen fibrillogenesis, 4,5) collagen deposition, 6) modulation of collagen stiffness, 7) and development and maintenance of elastic fibers. 8) The serum form of TNX has also been identified in humans and mice.…”
mentioning
confidence: 99%